2015
DOI: 10.1002/srin.201500263
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Strength, Crack Initiation, and Localized Plastic Fatigue Damage in VHCF of Duplex Stainless Steels

Abstract: The fatigue strength of two-duplex stainless steel grades, 2304 SRG and LDX 2101, with austenitic-ferritic microstructure is tested using ultrasonic fatigue testing equipment operating at 20 kHz. The testing is conducted in tension-compression mode with the load ratio R ¼ À1. The fatigue strength is evaluated at 10 7 , 10 8 , and 10 9 load cycles and the estimates of fatigue strength are higher for the LDX 2101 grade. The fatigue crack initiation mechanisms are analyzed using a scanning electron microscope. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…For metallic materials containing internal inclusions (Type I) as classified by Mughrabi [6], the fatigue crack initiation in the VHCF regime is commonly caused by subsurface or interior inclusion surrounded by a rough region of the fine granular area (FGA) [7][8][9][10]. For the type II materials without any inclusion in the interior, fatigue failure is strongly influenced by accumulated micro-plasticity due to microstructural heterogeneity and basically initiated from slip bands at the surface or subsurface [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…For metallic materials containing internal inclusions (Type I) as classified by Mughrabi [6], the fatigue crack initiation in the VHCF regime is commonly caused by subsurface or interior inclusion surrounded by a rough region of the fine granular area (FGA) [7][8][9][10]. For the type II materials without any inclusion in the interior, fatigue failure is strongly influenced by accumulated micro-plasticity due to microstructural heterogeneity and basically initiated from slip bands at the surface or subsurface [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, 10 a transient dynamic analysis has been applied where the J‐integral and thereby the SIF at a crack in a fatigue crack growth (FCG) bar specimen has been computed. In References 11–13 the same simulation procedure (transient dynamic) has been used to conduct stress–strain analysis in 20 kHz fatigue strength hourglass specimens. Such analysis is computationally inefficient, especially when small values of material damping are used, and a large number of cycles are required to pass the transients and reach the steady state oscillation.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, it has been reported that the interface characteristics, which depend on the orientation relationship (OR) between the two crystals, have a great effect on the dislocation slip behavior, fatigue behavior, and dynamic restoration process of DSS . The crystallographic OR between WA and ferrite in DSS has been studied in depth.…”
Section: Introductionmentioning
confidence: 99%